Good Enough Governance Revisited - and Grindle, Merilee S. (Development Policy Review, 2007)
The concept of good enough governance provides a platform for questioning the long menu of institutional changes and capacity-building initiatives currently deemed important (or essential) for development. Nevertheless, it falls short of being a tool to explore what, specifically, needs to be done in any real world context. Thus, as argued by the author in 2004, given the limited resources of money, time, knowledge, and human and organisational capacities, practitioners are correct in searching for the best ways to move towards better governance in a particular country context. This article suggests that the feasibility of particular interventions can be assessed by analysing the context for change and the implications of the content of the intervention being considered.